CURCUMA PRASINA (ZINGIBERACEAE), A NEW SPECIES FROM THAILAND - Leong-Škorničková, J.; Middleton, D.J.; Triboun, P.; Suddee, S. (Edinburgh Journal of Botany, 2017)
Curcuma prasina (Zingiberaceae), a stenoendemic species from Thailand, is described and illustrated here. It differs from other similar species in Curcuma subgenus Hitcheniopsis in Thailand in its inflorescences composed of fertile green bracts only (lacking any white coma bracts), purple staminodes, and purple labellum with a bright yellow centre extending from the base to about two-thirds of the labellum towards the apex.
Keywords: Curcuma gracillima; Curcuma larsenii; Curcuma parviflora; Curcuma pygmaea; Curcuma subg. Hitcheniopsis; Phu Wua Wildlife Sanctuary